2006
DOI: 10.1007/s00248-006-9016-1
|View full text |Cite
|
Sign up to set email alerts
|

Aeroterrestrial Microalgae Growing in Biofilms on Facades—Response to Temperature and Water Stress

Abstract: The photosynthetic performance of a microalgal biofilm colonizing a building facade was investigated between February and July 2004, with an emphasis on changing water availability and air humidity. The fluorimetric measurements of the quantum efficiency (F (v)/F (m)) indicated diurnal activity patterns. At most sampling dates the algal biofilm photosynthesized particularly in the morning and substantially less in the afternoon. As long as liquid water was present, the microalgae exhibited at least some degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 34 publications
7
47
0
Order By: Relevance
“…In our opinion, the position of the samples especially brings into play the diVerent forces of adhesion for the immersed samples at half, where there exists a gradient of moisture on the surface of the material between the immersed part and the air part. This case is similar to the one described by Haubner et al [11] when they studied aeroterrestrial microalgae growing in bioWlms on facades in the interface between hard substrata and the atmosphere. They concluded that this phenomenon was a response to temperature and water stress.…”
Section: Resultssupporting
confidence: 63%
“…In our opinion, the position of the samples especially brings into play the diVerent forces of adhesion for the immersed samples at half, where there exists a gradient of moisture on the surface of the material between the immersed part and the air part. This case is similar to the one described by Haubner et al [11] when they studied aeroterrestrial microalgae growing in bioWlms on facades in the interface between hard substrata and the atmosphere. They concluded that this phenomenon was a response to temperature and water stress.…”
Section: Resultssupporting
confidence: 63%
“…The other attributes of tree bark (besides pH) that may be responsible for the observed variation remain unknown. LüTTGe &BüdeL (2010) andhäuBNer et al (2006) found that varying tolerance to desiccation stress may be a key factor determining the survival ability of microalgal taxa in aerial biofilms. The tree species-dependent bark water-holding capacity (related to bark thickness, hardness, texture and stability) and stem flow (resulting from tree crown morphology) directly influence the intensity of desiccation stress and are important determinants of the distribution of various bark-dwelling organisms (valová & Bieleszová 2008;Büdel 2011;ellis 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Terrestrial algae often develop thick cell walls (Karsten & Holzinger, 2014), in many cases with mucilage layers or with incorporated macromolecules such as sporopollenins or sporopollenin-like substances (algenans) that might absorb the UVR (VanWinkle-Swift & Rickoll, 1997;Pescheck et al, 2010). In addition, under natural conditions, terrestrial green algae are most often incorporated into biofilms, while Klebsormidium species can form multi-layered structures on top of or interwoven with the upper millimetres of soil particles (Häubner et al, 2006). Both microstructures most probably contribute to a high degree of self-shading and hence photoprotection of individual cells inside such a population.…”
Section: Uv-sunscreens In Klebsormidiophyceae 283mentioning
confidence: 99%